2014
DOI: 10.1128/jvi.01717-14
|View full text |Cite
|
Sign up to set email alerts
|

Classic Nuclear Localization Signals and a Novel Nuclear Localization Motif Are Required for Nuclear Transport of Porcine Parvovirus Capsid Proteins

Abstract: Nuclear targeting of capsid proteins (VPs) is important for genome delivery and precedes assembly in the replication cycle of porcine parvovirus (PPV). Clusters of basic amino acids, corresponding to potential nuclear localization signals (NLS), were found only in the unique region of VP1 (VP1up, for VP1 unique part). Of the five identified basic regions (BR), three were important for nuclear localization of VP1up: BR1 was a classic Pat7 NLS, and the combination of BR4 and BR5 was a classic bipartite NLS. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 35 publications
3
41
0
Order By: Relevance
“…Of the three structural proteins, VP2 is the major capsid protein. It automatically assembles into virus-like particles (VLPs) and contains a novel nuclear localization motif, which is critical for the assembly of newly virions during viral proliferation (Boisvert et al 2014;Maranga et al 2003). Most importantly, the PPV1 VP2 protein plays a dominant role in eliciting neutralizing antibodies against viral infection (Antonis et al 2006;Rueda et al 2000;Xu and Li 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Of the three structural proteins, VP2 is the major capsid protein. It automatically assembles into virus-like particles (VLPs) and contains a novel nuclear localization motif, which is critical for the assembly of newly virions during viral proliferation (Boisvert et al 2014;Maranga et al 2003). Most importantly, the PPV1 VP2 protein plays a dominant role in eliciting neutralizing antibodies against viral infection (Antonis et al 2006;Rueda et al 2000;Xu and Li 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The sequences of the BCs are highly conserved among parvoviruses; thus, we inferred that the BC elements, which contain the NLS, most likely participate in the nuclear transport in other representative parvoviruses, as well. A recent study showed that the PPV was distinctly different from the closely related parvoviruses because the PPV had more than one activated NLS, including a novel nuclear localization motif (NLM) [ 42 ]. One of the NLSs is typically located on the VP1 N-terminal and plays a role in the early steps of infection, whereas the other NLS is a novel NLM that targets the VP2 trimers to the nucleus late in the infection [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…hnRNP K contains three repeats of a motif termed the KH domain (for K homology) (19), which could recognize single-stranded DNA or RNA. In addition, hnRNP K has a nuclear-localization signal (NLS) and a nuclear shuttling domain (KNS) which allow transport from the cytoplasm to the nucleus (20). Due to these different structures, hnRNP K is involved in translational modifications, including methylation, sumoylation and phosphorylation.…”
Section: Discussionmentioning
confidence: 99%